2013
DOI: 10.1007/978-3-319-00972-8_28
|View full text |Cite
|
Sign up to set email alerts
|

The Malta-Sicily Escarpment: Mass Movement Dynamics in a Sediment-Undersupplied Margin

Abstract: The Malta-Sicily Escarpment (MSE) is a steep carbonate escarpment that appears to have largely remained isolated from inputs of fluvial and littoral sediments since the Messinian Salinity Crisis. Mass movement activity has so far only been inferred from sediment cores at the base of the MSE. In this study we use geophysical and sedimentological data acquired from the upper MSE and outer Malta Plateau to: (i) map and characterise the dominant forms of mass movements, and (ii) determine the nature and origin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Swath bathymetry data were acquired from 370 km 2 of seafloor using a Kongsberg Simrad EM710 multibeam echosounder with a nominal sonar frequency of 70-100 kHz (Micallef et al 2013). An ROV dive was carried out to obtain video footage and still photographs of small-scale morphology, benthic habitats and biota from the canyon heads in order to ground-truth the acoustic data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Swath bathymetry data were acquired from 370 km 2 of seafloor using a Kongsberg Simrad EM710 multibeam echosounder with a nominal sonar frequency of 70-100 kHz (Micallef et al 2013). An ROV dive was carried out to obtain video footage and still photographs of small-scale morphology, benthic habitats and biota from the canyon heads in order to ground-truth the acoustic data.…”
Section: Methodsmentioning
confidence: 99%
“…Landslide activity across the Malta Escarpment had mainly been inferred from sediment cores, with turbidites, megaturbidites and debris flows being reported from the base of the Malta Escarpment (Scandone et al 1981;Casero et al 1984;Rebesco et al 2000). More recently, submarine landslides, in the form of translational slides, spreads and debris flows, have been shown to be a widespread geomorphologic phenomenon across the outer Malta Plateau and upper Malta Escarpment (Micallef et al 2013). The outer Malta Plateau also hosts four channels and a number of straight to non-linear bedrock ridges (Micallef et al 2013).…”
Section: Regional Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Dense seismic profiles have shown that, onshore and offshore, the region is characterized by three main well-defined sediment layers and a complex system of faults (Argnani et al, 2002) where the E1693 hypocentre could be well accomodated. The three layers are, (i) the Mesozoic carbonate sediment, (ii) the Cenozoic basin sediments and (iii) the Plio-Quaternary sediments (Argnani and Bonazzi, 2005;Micallef et al, 2014). The last layer composes the seafloor and we assume that the sliding mass could have involved only sediments of the Quaternary Period.…”
Section: Geological Settingmentioning
confidence: 99%
“…In this paper we address the hypothesis that, by influencing pore pressure in sub-seafloor sediment, shallow gas can promote the development of a weak layer above which submarine spreading can occur. Nevertheless, the characteristic submarine spreading morphology, in the form of a recurring pattern of ridges and troughs, can be observed in numerous submarine landslides around the world (Lastras et al 2003(Lastras et al , 2006Micallef et al 2013;Piper et al 1999;. 42.1).…”
Section: Introductionmentioning
confidence: 99%